2017
DOI: 10.1136/bjsports-2016-097434
|View full text |Cite
|
Sign up to set email alerts
|

Reducing musculoskeletal injury and concussion risk in schoolboy rugby players with a pre-activity movement control exercise programme: a cluster randomised controlled trial

Abstract: BackgroundInjury risk in youth rugby has received much attention, highlighting the importance of establishing evidence-based injury reduction strategies.AimTo determine the efficacy of a movement control exercise programme in reducing injuries in youth rugby players and to investigate the effect of programme dose on injury measures.MethodsIn a cluster-randomised controlled trial, 40 independent schools (118 teams, 3188 players aged 14–18 years) were allocated to receive either the intervention or a reference p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
216
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(242 citation statements)
references
References 47 publications
3
216
3
2
Order By: Relevance
“…Hislop et al ’s advice that ‘further research is required to further understand the contexts into which the exercise programme would be implemented, as well as identifying what factors may facilitate or inhibit programme use’1 should be heeded by policy makers seeking to implement the findings. While a shift in focus towards the primary prevention of injuries in rugby is welcome, this preactivity exercise programme is not a sufficiently evidenced solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hislop et al ’s advice that ‘further research is required to further understand the contexts into which the exercise programme would be implemented, as well as identifying what factors may facilitate or inhibit programme use’1 should be heeded by policy makers seeking to implement the findings. While a shift in focus towards the primary prevention of injuries in rugby is welcome, this preactivity exercise programme is not a sufficiently evidenced solution.…”
Section: Resultsmentioning
confidence: 99%
“…All efforts to reduce injuries in school rugby are welcome and the cluster randomised controlled trial by Hislop and colleagues deserves attention 1. Here, the authors presented a preactivity exercise programme that trained strength, agility and balance, with reductions in time-loss injuries and concussions claimed.…”
mentioning
confidence: 99%
“…Hislop and colleagues4 do not mention the cluster randomised trial design effect in relation to either the sample size calculation or data analysis. Attwood et al 5 however, mention that the sample size calculation was adjusted for a cluster coefficient (between-cluster coefficient of variation which is closely related to intracluster correlation coefficient) of 0.26.…”
Section: Design Effectmentioning
confidence: 99%
“…The risk of random confounding is generally greater in cluster randomised trials than individual randomised trials as the number of clusters is often small 3. Both Hislop et al 4 and Attwood et al 5 papers presented the baseline characteristics of participants in table 1, but they did not adjust for non-negligible imbalances in some baseline characteristics in their analysis 9. Confusingly, Hislop et al 4 paper reported p values for baseline comparisons (some of which were significant at 5% level), a common misuse of p values in the randomised trial literature.…”
Section: Adjustment For Baseline Imbalancementioning
confidence: 99%
“…As this intervention was found feasible by volleyball players and coaches, a randomized controlled trial has been initiated in order to evaluate its effectiveness on the occurrence of injuries among recreational adult volleyball players [25]. In rugby, a recent study showed that a preventive movement control exercise programme reduced match injury outcomes among young rugby players [26]. With regard to the conceptual similarities with especially the FIFA11+, one might be confident that 'Warming-Up Hockey' will lead to the reduction of lower extremity injuries among young and adult recreational field hockey players.…”
Section: Necessary Alterations To Warming-up Hockeymentioning
confidence: 99%